Transformative Resilience: An Overview of Its Structure, Evolution, and Trends - Asadzadeh, Asad; Khavarian-Garmsir, Amir Reza; Sharifi, Ayyoob; Salehi, Pourya; Kötter, Theo (Sustainability, 2022)
Transformational resilience is at the forefront of academic and policy initiatives on sustainable development, climate adaptation, and disaster risk reduction as a result of successive and complex changes in global dynamics. While the literature on transformative resilience is growing, there is no comprehensive analysis of its trends and development. This paper aims to close this knowledge gap by presenting a multifaceted bibliometric overview of transformative resilience literature, revealing its trends, focus areas, transitions, and intellectual foundations. This is based on 415 Web of Science-indexed articles published between 1996 and 2021. According to the findings, the concept has developed primarily around four key presentive domains: vulnerability and climate change adaptation, urban and regional disaster resilience, sustainability management and institutional transformation, and COVID-19. While priorities and subjects of research have evolved over time, key concepts such as resilience, adaptation, and climate change have recurred. Influential authors and documents from three interrelated resilience schools, including sustainable development, climate change adaptation, and disaster risk reduction, have shaped the field’s intellectual foundations. We contend that a greater variety of contexts is required to facilitate transformative resilience’s investigation, description, and experimentation.